The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/soc13040082
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Suicidal Ideation and Addiction to Various Social Media Platforms in a Sample of Young Adults: The Benefits of Physical Activity

Abstract: The rise in suicide death rates has become a major public health concern, which has led to increased addiction to internet and social media platforms. Despite the limited research available on the relationship between suicidal ideation and addiction to social media such as Instagram and TikTok, this study aims to examine this connection. The study design is cross-sectional, quantitative, comparative, and correlational, with a quasi-experimental approach. The sample includes 315 young adults aged 20 to 30 who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Moreover, Tiktok addiction was associated with decreased athletic participation in a study performed by Hudimova et al (2021) suggested that Tiktok addiction may delay athletes' engagement in regular athletic participation. Similar findings were also emerged by recent studies as well (Allahverdi, 2022;Mendes, Leonido, & Morgado, 2023).…”
Section: Literature Reviewsupporting
confidence: 91%
“…Moreover, Tiktok addiction was associated with decreased athletic participation in a study performed by Hudimova et al (2021) suggested that Tiktok addiction may delay athletes' engagement in regular athletic participation. Similar findings were also emerged by recent studies as well (Allahverdi, 2022;Mendes, Leonido, & Morgado, 2023).…”
Section: Literature Reviewsupporting
confidence: 91%
“…Sami et al (2018) also found a positive correlation between wish to attempt suicide and social networking sites. Mendes et al (2023) andPrasetyo et al (2021) tried to explore the phenomenon of social media use and its relationship with mental health. They all confirmed that internet addiction has a significant association with suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%